1979
DOI: 10.1007/bf01321566
|View full text |Cite
|
Sign up to set email alerts
|

A community program for the control of cardiovascular risk factors

Abstract: A community program for the control of cardiovascular risk factors, the CHAD program, was instituted in a family practice in western Jerusalem in 1971. The effectiveness of the program was evaluated by comparing the findings of community surveys conducted in 1970 and 1975 and by comparing the changes with those observed in an adjacent control neighborhood. This paper reports the findings among men aged 35 years and above. In the community exposed to the program there was a decrease in mean systolic and disatol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
2

Year Published

1983
1983
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 9 publications
0
23
0
2
Order By: Relevance
“…There were 33 studies 43,152,[154][155][156][157][158] of individual-level interventions (12 treatment, 132,133,135,136,138,141,142,147-150,155 21 prevention 43,[127][128][129][130][131]134,137,139,140,[143][144][145][146]152,154,[156][157][158] ); 60 studies 65,66,103,153,[159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]225,230,231 of communitylevel interventions (32 treatment, 153,159,160,164,…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…There were 33 studies 43,152,[154][155][156][157][158] of individual-level interventions (12 treatment, 132,133,135,136,138,141,142,147-150,155 21 prevention 43,[127][128][129][130][131]134,137,139,140,[143][144][145][146]152,154,[156][157][158] ); 60 studies 65,66,103,153,[159][160][161][162][163][164][165][166][167][168][169][170][171][172][173][174][175][176]225,230,231 of communitylevel interventions (32 treatment, 153,159,160,164,…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
“…Thirty-three 43,152,[154][155][156][157][158] individual-level studies were identified that met the review inclusion criteria. Because of heterogeneity in terms of study design and main outcomes, it was possible to conduct meta-analysis for only a small subset of studies in this category (n = 4 133,135,136,152 for weight change and n = 4 132,135,149,152 for BMI change, all targeted interventions).…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tidlig på 1970-tallet ble det gjennomført flere store intervensjonsstudier med primaerforebyggende hensikt, for eksempel Nord-Karelen prosjektet i Finland [47], CHAD-prosjektet i Israel [1] samt Stanford Three Community Project [14] og Franklin Community CVD Health Program I USA [48]. Studiene forsøkte å påvirke kostvaner, røykevaner og kroppsvekt samt risikofaktorer som hyperkolesterolemi og hypertensjon gjennom atferdsendringer i befolkningen, men resultatene har vaert varierende.…”
Section: Tiltak På Befolkningsnivåunclassified
“…Much has been learned about conducting community-based health promotion trials since the first generation of community-based studies, which tended to assess individual behavioral change within the community without taking into account the special factors that influence the power of community designs (2,87,114). Improvements in subsequent generations of community-based designs came about when researchers started to pay attention to the unit of randomization (the community), the interaction among individuals in the same community (intraclass correlation), and the special analytic techniques required for community studies (29,36,37,55,84).…”
mentioning
confidence: 99%